First Australian records of Ethusina (Crustacea: Decapoda: Ethusidae) and additional records from New Zealand - Ahyong, Shane T.; Farrelly, Caroline A. (Zootaxa, 2018)
Deep water ethusid crabs, genus Ethusina, are confirmed for the first time from Australia, with additional distribution records from New Zealand waters. Prior to the present study, Ethusina was reported from Australia on the basis of a single unidentified species from southwestern Australia. Four species are reported herein: Ethusina castro Ahyong, 2008, E. ciliacirrata Castro, 2005, E. robusta (Miers, 1886), and E. rowdeni Ahyong, 2008. Ethusina castro, previously known only from the female holotype from northern New Zealand is reported for the first time from eastern Australia, the Lord Howe Rise and Monowai Caldera, including the first known males. Ethusina ciliacirrata, described from Vanuatu, is confirmed from the Coral Sea and southwestern Australia. Ethusina rowdeni, from New Zealand, and the widespread E. robusta are recorded for the first time from Australia.